The Development of QR Code-Based Al-Qur'an Hadith and Fiqh Textbooks for Islamic Senior High School - Khofifah, Khofifah; Mistianingrum, Silfia Putri; Aisa, Aufia (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this research is to focus on innovation in the development of QR Code-based Al-Qur'an Hadith and Fiqh textbooks that are directly accessible via YouTube links so that students become more interested in learning independently and enthusiastic about the learning process. This research uses the RnD (Research and Development) method with a 4-D development model developed by Thiagarajan (define, design, develop, disseminate). Data collection techniques in this study were observation, interviews, questionnaires, pre-test, post-test, and documentation. The data analysis technique in this study is descriptive analysis and technical analysis of the Paired Sample T-Test. Based on the results of the validation that has been carried out, the development of my mother's teaching of Al-Qur'an Hadith and Fiqh QR Code was stated to be "very appropriate" with the percentage of material experts was 84% for Al-Quran Hadith and 179% for Fiqh while the assessment from material experts was 192%. Therefore, the development of teaching mothers is effectively and efficiently used as teaching materials or the latest references to increase students' interest in learning.